Photothermoacoustic effect: applied aspects of stressed state area diagnostics in structural materials - Alekseev, A.N.; Burbelo, R.M.; Zhabitenko, N.K.; Kuz‘mich, A.G. (Functional Materials, 2004)
Specific features of photothermoacoustic (PTA) transformation process in materials under stress have been studied in experiment and theoretically. Pulse and harmonic modulation regimen of laser emission have been considered. Basing on the results so obtained, a circuit design has been proposed for the stressed area PTA diagnostics in structural materials.